Analyzing sustainable urban development through smart and sustainable cities: an integrated review - Bashir, Muhammad Farhan; Ragmoun, Wided; Abdulaziz, Alfalih; Bashir, Madiha (Frontiers in Sustainable Cities, 2025)
‘Smart cities’ is an ever-evolving concept focusing on technological integration in urban policymaking to resolve contemporary urban issues. Despite repeated claims that ‘smart initiatives’ produce sustainability, a detailed research analysis is required to detail the extent to which the desired outcomes have been achieved. Within these academic, research, and policy parameters, the current study discusses the relevance of concepts of ‘smart’ and ‘sustainable cities’ through a systematic literature review to answer the inter-dependence of these concepts within modern urban reforms. Our findings highlight that cities cannot be ‘truly smart’ without becoming sustainable first, and technocentricity, complex policy practices, and ad-hoc conceptualization are the major hurdles in urban sustainability. Furthermore, urgent policy shifts remain key in long-term progressive sustainability goals. As urban policymaking has a wider socio-economic impact, smart and sustainable urban policymaking carries crucial implications for urban compliance and practices within the Sustainable Development Goals.